2016
DOI: 10.1007/s11517-016-1517-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slow and regular breathing exercise on cardiopulmonary coupling and blood pressure

Abstract: Meanwhile, BP was reduced significantly by the SPB procedure (SBP: from 122.0 ± 13.4 to 114.2 ± 14.9 mmHg, p < 0.001, DBP: from 82.2 ± 8.6 to 77.0 ± 9.8 mmHg, p < 0.001, PTT: from 172.8 ± 20.1 to 176.8 ± 19.2 ms, p < 0.001). Our results demonstrate that the SPB procedure can reduce BP and lengthen PTT significantly. Compared with amplitude dynamics, phase dynamics is a different marker for CPC analysis in reflecting cardiorespiratory coherence during slow breathing exercise. Our study provides a methodology to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
(68 reference statements)
1
24
0
Order By: Relevance
“…If the basic state is characterized by excessive excitability of sympathetic nerve, its excitability can be reduced, but if the vagus nerve activity is low, it can increase its activity, etc., so as to have a corresponding impact on BP and HR [48].Deep and slow mode VBE can increase parasympathetic activity, reduce sympathetic activity and improve cardiovascular function [26].VBE is not limited by time, place, auxiliary equipment, etc., which is one of the methods of lifestyle intervention. VBE is one of the frequently used alternative strategies for rehabilitation exercise of patients with cardiovascular diseases,which can be a new approach for comprehensive intervention of coronary heart disease [7,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the basic state is characterized by excessive excitability of sympathetic nerve, its excitability can be reduced, but if the vagus nerve activity is low, it can increase its activity, etc., so as to have a corresponding impact on BP and HR [48].Deep and slow mode VBE can increase parasympathetic activity, reduce sympathetic activity and improve cardiovascular function [26].VBE is not limited by time, place, auxiliary equipment, etc., which is one of the methods of lifestyle intervention. VBE is one of the frequently used alternative strategies for rehabilitation exercise of patients with cardiovascular diseases,which can be a new approach for comprehensive intervention of coronary heart disease [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…The research on the effect of respiration on HRV has become a hot topic in recent years [9][10].Previous studies have demonstrated that respiration is one of important influencing factors for HRV [11,12]. Cicek S et al [13] confirmed that deep and slow breathing can make people turn from depression to relaxation, and improve the regulation function of human organs or autonomic nerves, so as to improve the adaptability of human body.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has therapeutic advantages for cardiovascular, respiratory, and autonomic diseases, and allows for better psychological states (Courtney et al, 2011); furthermore, it helps improve HRV in patients with cardiovascular disorders (de Vidigal et al, 2016). Techniques that induce slow breathing have been used for centuries to provide health benefits due to the synchronization of key systems of the human body when slow-paced breathing is performed (Zhang et al, 2017). This study's results gave insights about the achievement of synchronization between cardiovascular and respiratory systems by volunteers that were not trained in the coherenceinducing technique of controlled breathing, even when the breathing pattern is hard to achieve (one respiration cycle every 10 s).…”
Section: Discussionmentioning
confidence: 99%
“…The research on the effect of respiration on HRV has become a hot topic in recent years [10,11].Previous studies have demonstrated that respiration is one of important influencing factors for HRV [12,13]. Cicek S et al [14] confirmed that deep and slow breathing can make people turn from depression to relaxation, and improve the regulation function of human organs or autonomic nerves, so as to improve the adaptability of human body.…”
Section: Introductionmentioning
confidence: 99%
“…During the follow-up, we will address the patient's doubts and evaluate the effectiveness of the intervention. Practice time: The total time per day is more than 30min [25], which can be delivered in batches, but at least 10 minutes at a time and at least 5 times a week [12].…”
mentioning
confidence: 99%